Lisbon agenda, regional innovation system and the new EU cohesion policy - Chang Woon Nam; Alina Schoenberg; Georg Wamser (Center for Economic Studies and ifo Institute (CESifo), 2011)
The EU's cohesion policy should now be confluent with the goals of the Lisbon strategy by promoting growth and employment. In this context, the promotion of a concept called regional innovation system has recently become important in the EU for guaranteeing long-term regional economic growth. This paper attempts to explain the determinants of the varying degrees of innovation promotion by the EU from one region to another. Since regional-policy strategies should have been subject to a new orientation towards more innovation promotion, we are particularly interested in whether the EU's co-financing policy of innovation projects changed for the 2007-2013 program period compared with the 2000-2006 period. According to our empirical analysis, which controls for various determinants of innovation promotion, there has been no significant change in the EU's regional policy strategy in general. We confirm this result when focusing on less-developed Objective 1 regions, where we would have expected the new policy strategy to show up more pronounced in particular.
Keywords: O18; O31; O52; R11; R58; 330; Lisbon Agenda; regional innovation network; EU cohesion policy; EU-Regionalpolitik; Lissabon Strategie; Innovationspolitik; EU-Staaten